Electron transfer between hemes in mammalian cytochrome c oxidase - Pilet, Eric (National Academy of Sciences, 2004)
Fast intraprotein electron transfer reactions associated with enzymatic catalysis are often difficult to synchronize and therefore to monitor directly in non-light-driven systems. However, in the mitochondrial respiratory enzyme cytochrome oxidase aa(3), the kinetics of the final electron transfer step into the active site can be determined: reverse electron flow between the close-lying and chemically identical hemes a(3) and a can be initiated by flash photolysis of CO from reduced heme a(3) under conditions where heme a is initially oxidized. To follow this reaction, we used transient absorption spectroscopy, with femtosecond time resolution and a time window extending to 4 ns. Comparison of the picosecond heme a(3)-CO photodissociation spectra under different redox states of heme a shows significant spectral interaction between both hemes, a phenomenon complicating the interpretation of spectral studies with low time resolution. Most importantly, we show that the intrinsic electron equilibration, corresponding to a ΔG(0) of 45-55 meV, occurs in 1.2 ± 0.1 ns. This is 3 orders of magnitude faster than the previously established equilibration phase of ≈3 μs, which we suggest to reflect a change in redox equilibrium closely following CO migration out of the active site. Our results allow testing a number of conflicting predictions regarding this reaction between both experimental and theoretical studies. We discuss the potential physiological relevance of fast equilibration associated with this low-driving-force redox reaction.